PENGARUH FINANCIAL KNOWLEDGE TERHADAP KINERJA USAHA YANG DIMEDIASI OLEH VARIABEL FINANCIAL CONFIDENCE, FINANCIAL SELF – EFFICACY, FINANCIAL ATTITUDE, DAN FINANCIAL BEHAVIOUR: (Studi Pada Pelaku Usaha Bisnis Online Bidang Kuliner di Kota Malang) - ZA, Zahroh (Jurusan Administrasi Publik, Fakultas Ilmu Administrasi, Universitas Brawijaya, 2024)
The Effect of Financial Knowledge on Business Performance as Mediated by the Variables Financial Confidence, Financial Self Efficacy, Financial Attitude and Fianncial Behavior. The Covid-19 pandemic that occurred in early 2020 had a negative impact on the business world, including the culinary business. Financial-related abilities are very necessary in an effective recovery strategy in the areas of knowledge, confidence, self-efficacy, attitude and behavior. The aim of this research is to analyze the influence of financial knowledge on business performance through several mediating variables, namely financial confidence, financial self- efficacy, financial attitude, and financial behavior among online business actors in the culinary sector in Malang City. This research methodology uses Partial Least Squares (PLS) analysis as a testing tool with WarpPLS statistical assets. The results of this study show that financial knowledge has a significant effect on financial confidence, financial self-efficacy and financial attitude, while financial confidence and financial attitude have a significant effect on financial behavior, but financial self-efficacy has no significant effect on financial behavior. Furthermore, financial knowledge and financial behavior influence business performance.